Description of Mercury Poison Clinical Symptoms in Workers and Communities Around the Small-Scale Gold Processing Area - Lensoni; Adlim; H Kamil; T Karma; Suhendrayatna (Proceedings of Malikussaleh International Conference on Multidisciplinary Studies (MICoMS), 2022)
The traditional gold processing process in Paya Seumantok Village, Krueng Sabee District, Aceh Jaya Regency, Aceh Province, is carried out using the amalgamation method which still uses mercury in the process, so it poses a risk to the health of workers and the surrounding community. This study aims to obtain an overview of the clinical symptoms experienced by workers and the community around the gold processing area. This study uses qualitative research methods with the number of community respondents were 90 respondents, and the number of worker respondents were 10 workers. Based on the results, the common acute clinical symptoms experienced by the community were headache (48.6%), cough (39.6%), abdominal pain (37.8%), diarrhea (29.7%), and hip pain (25.2%). While the chronic clinical symptoms experienced by the majority of community respondents were headaches (47.7%), irritability (27.9%), insomnia (26.1%), muscle cramps (23.4%), and weight loss (20.7%). Moreover, the most common acute clinical symptoms experienced by workers were cough (8 respondents), pelvic pain, diarrhea, abdominal pain, vomiting, nausea, and headaches were experienced by 7 respondents respectively. While for chronic clinical symptoms, the majority of workers experienced headaches and insomnia (8 respondents), irritability (6 respondents), anxiety (6 respondents), muscle cramps (5 respondents), and tremors (4 respondents). Based on the result, it can be concluded that the clinical symptoms encountered by the community and workers in the gold processing area have not shown clinical signs that are quite dangerous.